Interpretasi dan Bentuk Penyajian Lagu Habanera Dalam Opera Carmen Karya George Bizet Oleh Heny Janawati - Salsabilla, Salma Falista (Universitas Negeri Surabaya, 2020)
AbstractHabanera, one of the most famous songs in Opera Carmen, tells the love life of Carmen as the main role. Interestingly, the song Habanera was sung by an Indonesian mezzo-soprano singer from Bali, Heny Janawati, who has perform the Opera Carmen while singing in Europe and Indonesia with different interpretations and performance of song Habanera. The purpose of this study was to analyze the interpretation and performance form of the Habanera Opera Carmen song when it was performed in Jakarta in 2016 in order to become a knowledge. This research process used qualitative methods. The data in this study were obtained through observation, interviews, and documentations. Data analysis techniques used data reduction, data presentation, and data inference. As for the data validity test used triangulation. The results of this study indicate that Heny Janawati has characteristics to interpret this song through out the structure, tempo, dynamics, and intonation of this song. That she present in Opera Carmen are more modern from it's europe counterpart, which in Europe its characteristics, number of accompaniments, dimensions of the setting, lighting and wardrobe are more traditional.